1994
DOI: 10.1111/j.1365-3024.1994.tb00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD4+ T cell‐dependent anti‐erythrocyte antibody levels following the onset of parasite egg production in Schistosoma mansoni infected mice

Abstract: Anaemia has been reported to be a symptom of schistosomiasis mansoni. In other chronic infectious diseases, anti-red blood cell (RBC) antibodies have been suggested or shown to play a role in anaemia by participating in either complement or macrophage-dependent RBC elimination. To examine whether such a situation could be contributing to the anaemia of schistosomiasis, we examined RBC taken from infected mice for surface-bound antibodies. Our data show that prior to the onset of egg production infected mice ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…For example, the potent anti‐inflammatory agent dexamethasone reduces anaemia in experimentally infected mice (23). In addition, in schistosome‐infected mice and rabbits, anaemia is most pronounced during the acute phase of infection, but subsequently resolves as the infection enters the chronic phase and the intensity of the immune response modulates (24,25). In a murine model of hepatosplenic schistosomiasis, anaemia in some animals worsened as the infection became chronic (26).…”
Section: The Immunology Of Subtle Morbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the potent anti‐inflammatory agent dexamethasone reduces anaemia in experimentally infected mice (23). In addition, in schistosome‐infected mice and rabbits, anaemia is most pronounced during the acute phase of infection, but subsequently resolves as the infection enters the chronic phase and the intensity of the immune response modulates (24,25). In a murine model of hepatosplenic schistosomiasis, anaemia in some animals worsened as the infection became chronic (26).…”
Section: The Immunology Of Subtle Morbiditiesmentioning
confidence: 99%
“…Car washers in Kenya with high levels of S. mansoni infection report increased tolerance for certain food types following treatment with praziquantel (Dr Diana Karanja, personal communication). Other mechanisms suggested in schistosome‐related anaemia include development of antibodies against RBCs in schistosome‐infected mice (25), production of haemolytic factors by S. japonicum (28) and S. mansoni (29), haemolytic anaemia associated with splenomegaly (30), and iron‐deficiency anaemia brought about by malnutrition or blood loss in schistosomiasis patients (31).…”
Section: The Immunology Of Subtle Morbiditiesmentioning
confidence: 99%
“…Indeed, the sequence of TgHSP70 is 68.1 and 74.1% homologous to those of mouse HSP70 (mHSP70) and hHSC70, respectively (6,8,47,50); thus, it is possible that the high homology of HSP70 between T. gondii and hosts could induce autoreactive immune responses in T. gondii-infected hosts. Autoantibody induction against host components has been reported in infection with other parasites such as Trypanosoma cruzi (16), Plasmodium falciparum (21), Schistosoma mansoni (15), and Onchocerca volvulus (27). In particular, Mattei et al demonstrated that sera from humans infected with malaria recognized the human HSP70, indicating that autoantibodies directed against host HSP70 could be induced by the homologous parasite protein (21).…”
mentioning
confidence: 99%